Highlighting Financial Factoring in Indonesia from Islamic Perspectives: A Literature Review - Siradjuddin, Siradjuddin; Arif, Widyantono (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This article aims at investigating factoring from the Islamic perspectives in indonesia. This study applied normative juridical research with conceptual and legal approaches. The results reveals that the factoring based on the fatwa of National Sharia Council-Indonesian Ulama Council (NSC-IUC) No. 67, 2008 employs wakalah bil ujrah and hiwalah contract corresponding to Bank Indonesia Circular Letter (BICL) No. 10/14/DPbS. There are similarities between the fatwa of NSC-IUC and the formulation of BICL. They form the aspects, objects, other types, forms of agreement to provide bailouts (qardh) and get ujrah/costs, and the phase in the Civil Code is cessie and subrogation, while the difference is the form of debt transfer and receivables transfer, assignors, related agencies, the object of transactions, and differences with Hiwalah Muqayyadah that does not provide bailouts and ujrah, as well as dispute resolution.